Low Vocal Pitch Preference Drives First Impressions Irrespective of Context in Male Voices but Not in Female Voices. (August 2016) - Tsantani, Maria S.; Belin, Pascal; Paterson, Helena M.; McAleer, Phil
Vocal pitch has been found to influence judgments of perceived trustworthiness and dominance from a novel voice. However, the majority of findings arise from using only male voices and in context-specific scenarios. In two experiments, we first explore the influence of average vocal pitch on first-impression judgments of perceived trustworthiness and dominance, before establishing the existence of an overall preference for high or low pitch across genders. In Experiment 1, pairs of high- and low-pitched temporally reversed recordings of male and female vocal utterances were presented in a two-alternative forced-choice task. Results revealed a tendency to select the low-pitched voice over the high-pitched voice as more trustworthy, for both genders, and more dominant, for male voices only. Experiment 2 tested an overall preference for low-pitched voices, and whether judgments were modulated by speech content, using forward and reversed speech to manipulate context. Results revealed an overall preference for low pitch, irrespective of direction of speech, in male voices only. No such overall preference was found for female voices. We propose that an overall preference for low pitch is a default prior in male voices irrespective of context, whereas pitch preferences in female voices are more context- and situation-dependent. The present study confirms the important role of vocal pitch in the formation of first-impression personality judgments and advances understanding of the impact of context on pitch preferences across genders.